2019
DOI: 10.1155/2019/7436293
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Effective Fields of Two Ultra-Widefield Ophthalmoscopes, Optos 200Tx and Clarus 500

Abstract: Purpose To compare the effective fields of the Optos 200Tx® and Clarus 500™, two ultra-widefield ophthalmoscopes, based on their ability to image branches of retinal vessel in the four retinal quadrants. Methods Ninety retinal images from 90 patients with various eye diseases were studied. All patients had undergone 200° retinal imaging to obtain a single image of Optos (O) and the montage of two images of the Clarus (C). The highest number of traceable vessel branches in the four retinal quadrants was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Relative advantages of the Clarus compared to Optos are true-colour imaging and reduced eyelid or eyelash artefact, but relative disadvantages of the Clarus are a brighter light flash and a smaller field of capture of 133°from individual imagesalthough montaging increases the overall field of view [27]. One study reported that Optos images tend to capture retinal vascular detail in the superotemporal quadrant better than montaged Clarus images, which in turn may better capture retinal vascular detail in the inferonasal quadrant [32]. The implications of these findings for imaging of SCR (which preferentially affects the temporal retina) merit further study.…”
Section: Artificial Intelligence For Screening For Sickle Cell Retino...mentioning
confidence: 99%
“…Relative advantages of the Clarus compared to Optos are true-colour imaging and reduced eyelid or eyelash artefact, but relative disadvantages of the Clarus are a brighter light flash and a smaller field of capture of 133°from individual imagesalthough montaging increases the overall field of view [27]. One study reported that Optos images tend to capture retinal vascular detail in the superotemporal quadrant better than montaged Clarus images, which in turn may better capture retinal vascular detail in the inferonasal quadrant [32]. The implications of these findings for imaging of SCR (which preferentially affects the temporal retina) merit further study.…”
Section: Artificial Intelligence For Screening For Sickle Cell Retino...mentioning
confidence: 99%
“…When looking at lesions detected in zone C3, more lesions were detected by the Optos P200dTx, as it captures a wider field of view in a single image. 19 The lesser sensitivity of the Zeiss Clarus 500 in the temporal quadrant in this study is likely due to a lesser field of view for single images acquired in the temporal quadrant.…”
Section: Discussionmentioning
confidence: 79%
“…These findings could be due to the Optos P200dTx utilizing pseudocolor imaging with a resolution of 14 to 20 µm when compared with the Zeiss Clarus 500, which utilizes true color imaging with a resolution of 7 µm. 19 Additionally, the issues with identification of lesions anterior to the retina, such as vitreous hemorrhage, could be due to the technique of imaging, as the photographer aims to focus on the posterior pole, as well as by the fact that the Optos P200dTx captures the image as soon as the posterior pole is clearly imaged on the sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al described an advantage of the Optos in all quadrants compared to the Clarus with the largest additional area depicted in the temporal quadrant 15 . Matsui et al compared retinal vessel branches to determine the effective fields seen on both devices and found more retinal vessels in the superotemporal quadrant on the Optos 200Tx, compared to more in the inferonasal quadrant on the Clarus 500 25 . Using anatomical landmarks to compare images, we could also detect an advantage of the Optos in our temporal peripheral field F3.…”
Section: Discussionmentioning
confidence: 99%